ANALISIS KEPRIBADIAN GURU DAN PESERTA DIDIK KELAS 5 SDN 1 TONJONG - Nurkholis; Adzikri Frilla Akramullah; Muhammad Fadhli Qolbi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the influence of teachers’ personalities on the character development of fifth-grade students at SDN 1 Tonjong. Personality, derived from the term ‘persona’ in Latin, plays a crucial role in social interactions and learning within the school environment. Through a qualitative approach, this research involves interviews with teachers and students, classroom observations, and thematic analysis to identify the patterns of interaction that occur. The findings indicate that self-confidence, social support, social interaction, value teaching, and emotional management are key factors in the formation of students’ character. Teachers who can create a supportive and empathetic classroom atmosphere can enhance students’ self-confidence, strengthen social relationships, and teach positive values. These findings emphasize the importance of teachers’ roles in building students’ character and creating a productive learning environment. This research is expected to provide insights for educators and policymakers in efforts to improve the quality of education and the character development of students.